Using events to understand users : analytics for product managers (O'Reilly Media, 2018)
"This course explains how successful product managers, designers, and UX professionals use the analytics tool called event tracking to best understand how users interact and behave throughout the entire user journey. While the course focuses on Google Analytics-based event tracking, the lessons learned also apply to other analytics tools. The course describes the purpose of event tracking, how to set it up, and how to use it. It teaches you about interaction maps and how they help you understand when to use event tracking. It covers the distinctions between goals and events, and when to use an event versus a goal or an event-based goal. Packed with practical tips and tricks, this course will boost your ability to uncover deep insights into how your customers use and interact with your products."--Resource description page